2016
DOI: 10.1111/clr.12918
|View full text |Cite
|
Sign up to set email alerts
|

Differences in knowledge related to dental implants between patients with and without a treatment history of dental implants

Abstract: Patients without a treatment history of dental implants placed more importance on the preservation of healthy teeth. Because patients, in particular those without a treatment history of dental implants, are anxious about surgery, we should provide them with more information on treatment than we already do and explain the risks of treatment to them. To keep the credence between doctors and patients, informed consent and patient education on treatment are six important concerns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…Over 60% of the undergraduates who responded to the present questionnaire believed the life of these treatments is between 10 and 20 years, without significant difference between the groups, in contrast to the study by Chaudhary et al ( 6 ) in which only 39.8% answered the question in this way. Such opinions confirm the need for factual information so that undergraduates and post-graduates may give the patient realistic expectations for treatment, factors involved in the treatment, and about the risks involved in each individual case ( 11 ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Over 60% of the undergraduates who responded to the present questionnaire believed the life of these treatments is between 10 and 20 years, without significant difference between the groups, in contrast to the study by Chaudhary et al ( 6 ) in which only 39.8% answered the question in this way. Such opinions confirm the need for factual information so that undergraduates and post-graduates may give the patient realistic expectations for treatment, factors involved in the treatment, and about the risks involved in each individual case ( 11 ).…”
Section: Discussionmentioning
confidence: 69%
“…As the degree course advanced and students progress in their learning, they agreed that implant treatments are less aggressive than dental preparation procedures; this datum (59.8%) coincides with a population of dental undergraduates in India ( 6 ). Interestingly, this is the main reason why patients request this type of treatment, Ken ( 11 ) report that 32% of patients declared this to be the reason for choosing implant-based treatment, being the second reason a rejection of the option of removable prostheses, and the third because the treatment had been recommended by someone they knew. In a similar vein, the study also showed that most patients ignore some very important factors such as the fact that smoking has a negative impact on the life expectancy of the implant (48%), the risk of peri-implantitis (80%), or the fact that they believe that an implant-supported prosthesis has a long life of 20-25 years (52%) ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellis et al () reported that some participants in their study showed a sense of relative mistrust in the explanations given by professionals, who were regarded as only selling a product. Therefore, clinicians must inform their patients as clearly as possible and, especially for those without a treatment history of dental implants, the information must be provided in more detail than usual (Ken, Tachikawa, & Kasugai, ).…”
Section: Discussionmentioning
confidence: 99%
“…Same observation has been mentioned in the clinical trial conducted by Garcia-Blanco M. et al [8] . These findings can be attributed to the mechanical stimulation of nerve endings of the periodontal ligament surrounding the adjacent teeth [16] .…”
Section: Discussionmentioning
confidence: 99%